( x +3)^3+3 (x+3)=x (x+3)^2 помогите решить

0 голосов
20 просмотров

( x +3)^3+3 (x+3)=x (x+3)^2 помогите решить


Алгебра (14 баллов) | 20 просмотров
Дано ответов: 2
0 голосов

Вот держи. Вроде должно быть правильно.


image
image
(92 баллов)
0 голосов
( x +3)^3+3 (x+3)=x (x+3)^2 
x^3+9x^2+27x+27+3x+9=x(x^+6x+9)
x^3+9x^2+27x+27+3x+9=x^3+6x^2+x
9x^2+27x+27+3x+9=6x^2+9x
9x^2+30x+36=6x^2+9x
9x^2+30x+36-6x^2-9x=0
3(3x^2+10x+12-2x^2-3x)=0
3(x^2+7x+12)=0
3(x^2+4x+3x+12)=0
3(x(x+4)+3(x+4))=0
3(x+3)(x+4)=0
(x+3)(x+4)=0
x=-3
x=-4
(868 баллов)